Legal Challenges to the Implementation of Meritocracy in Organizational Governance - Dimas Ferry Anuraga; Suparto Wijoyo; Juansih; Deshinta Arrova Dewi (PT. Islamic Research Publiser, 2026)
Meritocracy is widely regarded as a fundamental principle of organizational governance because it promotes fairness, transparency, and competence in recruitment, promotion, and leadership selection. However, its implementation remains legally complex because merit-based systems must be reconciled with equality principles, labor rights, affirmative action, constitutional provisions, and institutional accountability. This study addresses the problem of fragmented understanding of the legal challenges surrounding meritocratic governance across different organizational and regulatory contexts. It asks: What are the principal legal challenges in implementing merit-based recruitment, promotion, and leadership selection across institutional and jurisdictional contexts? The study employs qualitative documentary analysis of legal, regulatory, institutional, and scholarly sources addressing meritocratic recruitment, promotion, and leadership selection across diverse governance contexts. The findings identify five interconnected challenges: balancing merit with equality and anti-discrimination requirements; reconciling meritocracy with affirmative action; ensuring transparency and accountability in personnel decisions; limiting political and institutional interference; and addressing legal risks associated with artificial intelligence in recruitment and personnel assessment. The synthesis further demonstrates that meritocracy is not a legally neutral or universally applicable principle, but is shaped by the interaction between merit criteria, equality obligations, institutional structures, and jurisdiction-specific regulations. Academically, this study contributes an integrative legal-governance perspective that conceptualizes meritocracy as a conditional institutional principle, providing a foundation for comparative research and the development of legally responsive merit-based governance systems.